Antibacterial efficacy of Zinc oxide nanoparticles against Escherichia coli experimental infection in broiler chickens - Shakal, Mohamed; Khalefa, Hanan S.; Salem, Heba (Journal of Advanced Veterinary Research, 2024)
A serious problem within the poultry sector is avian colibacillosis, which can be found either as a primary or secondary infection, inducing huge financial losses in poultry production and posing a zoonotic threat to humans. Escherichia coli (E. coli) avian pathogenic strains have recently demonstrated multi-drug resistance. Therefore, this investigation aimed to assess the efficacy of zinc oxide nanoparticles (ZnO-NPs) against avian pathogenic E. coli O78 in broiler chickens. Thus, 147 broiler chicks were allocated into seven groups, each with 21 birds with triplicates of seven birds each. In group G1, control birds are negative; in group G2, control-positive infected birds are positive for E. coli O87; G3, infected-supplied with 1 mg/L ZnO-NPs in drinking water; G4, infected-treated with 2 mg/L ZnO-NPs in drinking water; G5, infected-treated with antibiotics; G6, supplied for continuous 35 days with 1 mg/L ZnO-NPs; and G7 treated for continuous 35 days with 2 mg/L ZnO-NPs. Durin 5 weeks observation duration, bird performance, mortalities were monitored, and serum samples were gathered to evaluate the immune system. It was noticed that the birds treated with ZnO-NPs (G6 and G7) gained more weight (P = 0.017) and weighed significantly more than the control-infected birds (G2). On days 1 through 35, there was a significant improvement in the FCR of the infected birds that supplied with ZnO-NPs (G4, G6, and G7) (P =0.034). HI titers did not differ between the groups at 21 and 28 days. In conclusion, in comparison to the non-treated group, treatment with both doses of ZnO-NPs led to reduction in the colonization of E. coli in the intestine and cecum, a reduction in the severity of clinical signs, & mortalities, as well as improve birds’ performance but no significant differences in humoral immune response against ND vaccine among different groups.